2019
DOI: 10.3390/ijgi8020071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Influence of Disturbances on Forest Vegetation Using the Time Series of Landsat Data: A Comparison Study of the Low Tatras and Sumava National Parks

Abstract: This study focused on the evaluation of forest vegetation changes from 1992 to 2015 in the Low Tatras National Park (NAPANT) in Slovakia and the Sumava National Park in Czechia using a time series (TS) of Landsat images. The study area was damaged by wind and bark beetle calamities, which strongly influenced the health state of the forest vegetation at the end of the 20th and beginning of the 21st century. The analysis of the time series was based on the ten selected vegetation indices in different types of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Concerning the processing of the data with a lower temporal resolution (such as Landsat), several preprocessing steps for preparing the datasets are necessary. To obtain comparable results, it is necessary to use normalization [20,62,63], cross-calibration methods, specialized harmonizing algorithms (like LandsatLinkr [29]), or to use other methods (like LandTrendr [64,65]). However, in the case of the Sentinel-2 data, normalization methods were not necessary for processing for the TS when using the entire set of measurements with a high temporal resolution (outliers caused by inhomogeneity of the environment during the year may be filtered out-or the data may be fit).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Concerning the processing of the data with a lower temporal resolution (such as Landsat), several preprocessing steps for preparing the datasets are necessary. To obtain comparable results, it is necessary to use normalization [20,62,63], cross-calibration methods, specialized harmonizing algorithms (like LandsatLinkr [29]), or to use other methods (like LandTrendr [64,65]). However, in the case of the Sentinel-2 data, normalization methods were not necessary for processing for the TS when using the entire set of measurements with a high temporal resolution (outliers caused by inhomogeneity of the environment during the year may be filtered out-or the data may be fit).…”
Section: Discussionmentioning
confidence: 99%
“…These indices were selected on the basis of the above-mentioned publications as the most recommended remote sensing indices for assessing the health of the vegetation. The NDMI vegetation index was designed to investigate the changes in the physiology of the vegetation and so this should be a suitable indicator to detect the disturbances in the forest [20]. The combination of the NIR with the SWIR removed variations induced by the leaf internal structure and leaf dry matter content, improving the accuracy in retrieving the vegetation water content.…”
Section: Ts Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For the remaining indices, spatial resolution was set at 10 m by resampling lower resolution band pixels with the Nearest Neighbour algorithm with "r.resample" function in order to lose as little resolution as possible, considered the reduced extension of sampled sites. These indices take advantage of SWIR, NIR and RED, which have been proven highly effective in the detection of storm damages [22]. The indices used in this study are reported in Table 2.…”
Section: Remote Sensing Datamentioning
confidence: 99%